Identifying Critical Factors Contributing to Export Logistics Disruptions: A 6M Fishbone Analysis of Freight Forwarder Operations in Seaborne Shipping at PT. Q Logs Indonesia - Kastian, Muhammad Aris; Pakonglean, Rita; Ningrat, Andi; Syahrir, M. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The export logistics process in seaborne shipping is highly complex, influenced by numerous factors that can affect efficiency, timeliness, and safety of shipments. Freight forwarders, such as PT. Q Logs Indonesia, play a crucial role in managing and ensuring the smooth movement of export shipments across borders. This study aims to identify and analyze key factors that contribute to disruptions in the shipping process, using the Fishbone (Ishikawa) diagram as a tool. The diagram categorizes potential causes into six main areas: Man (Human Resources), Method (Work Methods), Machine (Equipment and Systems), Materials (Documents and Goods), Mother Nature (Environmental and Regulatory Factors), and Management (Policy and Coordination). Data was collected through interviews, observations, and document analysis. The research identifies several root causes of logistical inefficiencies, including inadequate training, inefficient procedures, outdated systems, document errors, regulatory changes, and mismanagement. By mapping these issues using the Fishbone diagram, the study provides valuable insights into the underlying causes of delays and disruptions in the export logistics process. The findings offer practical recommendations for PT. Q Logs Indonesia to address operational bottlenecks, streamline procedures, and improve the overall reliability and efficiency of seaborne export logistics. These insights are expected to help the company optimize its export operations, reduce delays, and enhance service delivery to customers.